If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + -7p = -7p(p + -1) Reorder the terms: 14 + -7p = -7p(-1 + p) 14 + -7p = (-1 * -7p + p * -7p) 14 + -7p = (7p + -7p2) Solving 14 + -7p = 7p + -7p2 Solving for variable 'p'. Combine like terms: -7p + -7p = -14p 14 + -14p + 7p2 = 7p + -7p2 + -7p + 7p2 Reorder the terms: 14 + -14p + 7p2 = 7p + -7p + -7p2 + 7p2 Combine like terms: 7p + -7p = 0 14 + -14p + 7p2 = 0 + -7p2 + 7p2 14 + -14p + 7p2 = -7p2 + 7p2 Combine like terms: -7p2 + 7p2 = 0 14 + -14p + 7p2 = 0 Factor out the Greatest Common Factor (GCF), '7'. 7(2 + -2p + p2) = 0 Ignore the factor 7.Subproblem 1
Set the factor '(2 + -2p + p2)' equal to zero and attempt to solve: Simplifying 2 + -2p + p2 = 0 Solving 2 + -2p + p2 = 0 Begin completing the square. Move the constant term to the right: Add '-2' to each side of the equation. 2 + -2p + -2 + p2 = 0 + -2 Reorder the terms: 2 + -2 + -2p + p2 = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -2p + p2 = 0 + -2 -2p + p2 = 0 + -2 Combine like terms: 0 + -2 = -2 -2p + p2 = -2 The p term is -2p. Take half its coefficient (-1). Square it (1) and add it to both sides. Add '1' to each side of the equation. -2p + 1 + p2 = -2 + 1 Reorder the terms: 1 + -2p + p2 = -2 + 1 Combine like terms: -2 + 1 = -1 1 + -2p + p2 = -1 Factor a perfect square on the left side: (p + -1)(p + -1) = -1 Can't calculate square root of the right side. The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 3a-7z=6 | | (12x-8)= | | -6g+30=6 | | .30/(y-1.43)=x | | r+441=-225 | | 11w-13w=12 | | 1+7a=1+4a+2a-5 | | -5y+2=37 | | N+9=3*6 | | 3(w-2)+4=2w+5 | | k/24=25 | | 26q=-832 | | 7x+25=3x+50 | | -7-7x+4x=-25 | | z=1+2i | | 6x+3.8=1x+19 | | -3x^2+12x+1=y | | 11w-13=12 | | 8x+9=3x+1+4x+5 | | m+4=57 | | f(3)=3(3)+2 | | 4(p-3)=-16 | | 2p=56 | | 7=k+1/8 | | 4x-8=7x+10 | | -13-8b=3-3b-7b | | 2a+6z=4 | | X+5+3x=x | | 4t-1=-3+6T | | 2(3x+5)=4x-5+17 | | X+5=9x | | 2h-3=-11 |